Definição, avaliação do pensamento computacional e sua relação com a ansiedade matemática em estudantes dos anos finais do ensino fundamental - Alves, Karina Lumena de Freitas (2025)
Computational Thinking (CT) has gained increasing relevance in education, being globally recognized as essential in the 21st century. Several countries, including Brazil, have been seeking to incorporate CT into their educational curricula. However, despite the growing interest, there is still no clear consensus on its definition. Furthermore, mathematical anxiety (MA), which affects a significant number of students worldwide, can hinder learning and, consequently, the development of CT in the area of mathematics. Although MA has also been widely studied, there are no studies in the literature that investigate the relationship between CT and MA together, which constitutes an important gap that this research seeks to fill. This research has two main objectives: (1) to present an operational definition of CT in the context of school mathematics, and (2) to empirically investigate possible associations between CT and MA. To achieve the first objective, Study 1 was conducted through a scoping review. After applying strict inclusion and exclusion criteria, 15 studies were selected. The results indicated that the definitions of CT found in the literature highlight crucial skills for its development, such as problem decomposition, pattern recognition, abstraction, and algorithms. The operational definition proposed in this study aligns with the one presented by Brackmann (2017), which was adopted by the Brazilian Center for Innovation in Education (CIEB). Study 2 aimed to translate and adapt the Computational Thinking Test (TPC) to the Brazilian context, given the scarcity of specific instruments to measure CT. The TPC, initially developed and validated in Spain, was adjusted to ensure reliability in this research. Finally, Study 3 investigated the relationship between CT and MA in 320 students from the 6th to the 9th grade of elementary school, using the adapted TPC and the Mathematical Anxiety Scale (MAS). This correlational study revealed a moderate negative correlation between CT and MA (Spearman coefficient = -0.31), indicating that students with higher levels of MA tend to exhibit lower levels of CT. Additionally, other findings were identified: boys showed higher levels of CT, while girls exhibited higher levels of MA. Another important discovery was that students from private schools showed higher levels of CT compared to those from public schools, indicating a possible inequality in access to resources that foster the development of CT. In summary, the main contribution of this thesis is to provide empirical evidence of the relationship between CT and MA. These results pave the way for future research to investigate strategies for teaching CT with the goal of reducing MA, improving students’ self-efficacy in mathematics, and promoting a more inclusive learning environment. The adaptation of the TPC also provides a valuable tool for future CT assessments in Brazil, expanding research possibilities and educational practices in the context of mathematics education.